Investigation of mechanical and thermal properties of rare earth pyrochlore oxides by first‐principles calculations. Issue 5 (8th October 2018) - Yang, Lan; Zhu, Changhua; Sheng, Ye; Nian, Hongqiang; Li, Qian; Song, Peng; Lu, Wencong; Yang, Jiong; Liu, Bin
Abstract: The pyrochlore‐type rare‐earth oxides attract considerable attentions due to their outstanding properties and extensive applications. In this work, contour maps of mechanical/thermal properties as a function of A and B cation radii across a wide variety of A 2 B 2 O7 ( A  = La‐Lu and Y; B  = Ti, Sn, Hf, Zr, Pr and Ce) pyrochlore oxides are studied using the first‐principles calculations. The mechanical/thermal properties vary dramatically with increasing of the B cation sizes but do not show a strong systematic dependence on the A cation sizes. Furthermore, the machine learning algorithm is performed for the large family of pyrochlores and the parameters playing key role on mechanical/thermal properties are clarified. Besides, the expressions of focused mechanical and thermal properties are constructed. These results are expected to guide the future material design through composition tailoring.